Fretting Fatigue: Current Technology and Practices 2000
DOI: 10.1520/stp14735s
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Fretting Crack Nucleation in Aerospace Alloys with Emphasis on Life Prediction

Abstract: A statistically-designed experimental program engendered to validate an analytical approach for the prediction of fretting crack nucleation in 2024-T351 aluminum alloy has been completed. The test results indicate that the near-surface cyclic contact stress and strain field can be juxtaposed with a multiaxial fatigue life parameter relying on uniaxial strain-life constants to predict crack nucleation for a wide range of load intensities and conditions representative of those experienced in riveted joints. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Figure 14 solidi es a quantitative link between rivet process parameters and fatigue performance by presenting fatigue lifetimes of 12 single-lap joints manufactured with varied and controlled squeeze forces and tested to failurein a separate study. 4 As shouldbe anticipated, fatigue life decreased with an increase in applied load. In addition,joint life increasedwith larger maximum squeezeforces.…”
Section: Model Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Figure 14 solidi es a quantitative link between rivet process parameters and fatigue performance by presenting fatigue lifetimes of 12 single-lap joints manufactured with varied and controlled squeeze forces and tested to failurein a separate study. 4 As shouldbe anticipated, fatigue life decreased with an increase in applied load. In addition,joint life increasedwith larger maximum squeezeforces.…”
Section: Model Resultsmentioning
confidence: 78%
“…This quantitative assessment of the localized conditions has been used successfully with a fatigue life parameter to predict the fatigue performance of riveted single-lap joint structures manufactured under controlled conditions. 4,19 Conclusions A nite element model of force-controlled rivet installation has been formulated in a commercially available analysis package and veri ed with a series of well-characterized experiments. Results from this analysis reveal a distinct through-thickness dependence of the residual stress eld, contrary to assumptions prevalent in the literature and critical to understanding the nature of fatigue crack nucleation and propagation around the rivet/hole interface.…”
Section: Model Resultsmentioning
confidence: 99%
“…It is observed that increasing D c will increase the life of material specimen. The SN curves for Al 2024 are compared with the experimental data obtained by Szolwinski et al [24]. S45C curves are compared with experiments done by Sato et al [25].…”
Section: Resultsmentioning
confidence: 88%
“…It is most commonly found in all kinds of press fits, spline connections, leaf springs, riveted and bolted joints, nuclear fuel elements and also in wire ropes. The most significant factor in a contact with fretting is the coefficient of friction [2]. This factor is influenced by the surface quality, the wear induced by the fretting, the behavior of the third body, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This factor is influenced by the surface quality, the wear induced by the fretting, the behavior of the third body, etc. Many studies have been completed for characterizing friction in fretting tests [2]. In the numerical studies dealing with fretting, the COF is generally presented as a constant of the contact [3,4].…”
Section: Introductionmentioning
confidence: 99%